2013
DOI: 10.1177/1534765612455228
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in the U.S. Warfighter: Sensitivity to punishment and antidepressant use contribute to decision-making performance.

Abstract: Little research has been done to explore the integrity of emotion-based decision-making performance in individuals with posttraumatic stress disorder (PTSD). In the current study, performance on two decision-making tasks with both positive and negative reinforcement, the standard Iowa Gambling Task (IGT) and the variant Iowa Gambling Task (vIGT), and measures of mood symptoms, were compared between U.S. active-duty soldiers diagnosed with PTSD (n = 23) and soldiers with no PTSD (n = 23). The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Two advantageous decks yield high immediate losses but also higher delayed earning (net gain), and two disadvantageous decks present smaller immediate losses but also smaller gains (net loss). Dretsch et al (2012) found that individuals with PTSD performed similar to nondiagnosed controls on the standard IGT but performed worse than controls on the vIGT.…”
Section: Pagementioning
confidence: 86%
See 2 more Smart Citations
“…Two advantageous decks yield high immediate losses but also higher delayed earning (net gain), and two disadvantageous decks present smaller immediate losses but also smaller gains (net loss). Dretsch et al (2012) found that individuals with PTSD performed similar to nondiagnosed controls on the standard IGT but performed worse than controls on the vIGT.…”
Section: Pagementioning
confidence: 86%
“…Research in reward processing has been extended to find that individuals with PTSD may also have a unique decision-making pattern (Dretsch, Thiel, Athy, Born, & Prue-Owens, 2012). Prior research has found evidence of decision-making impairments in other types of anxiety disorders (e.g., obsessive compulsive disorder; de Rocha, Alvarenga, Malloy-Diniz, & Corrêa, 2011), as well as major depressive disorder (Han et al, 2012).…”
Section: Pagementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hypersensitivity to threat seems plausible based on prior findings [36, 37, 66]. Prior findings in healthy individuals, have found that diminution of ROI activation to learned-threat is accompanied by diminution of related SCRs [23, 51].…”
Section: Discussionmentioning
confidence: 96%
“…Only limited evidence implicates the insula in PTSD as indicated by increased activation in response to predictable threat, potentially suggesting hypersensitivity to threats when they are predictable [32]. Behavioral evidence provides some support by showing that active-duty service members with PTSD have compromised emotion-based learning, which appears be attributed to hypersensitivity to threat saliency [36]. Psychophysiology findings also suggest that PTSD is associated with hypersensitivity to threat, which may be moderated by predictability as measured by startle response to aversive auditory stimuli [37].…”
Section: Introductionmentioning
confidence: 99%